Environmental control of autoimmune inflammation in the central nervous system. (December 2016) - Rothhammer, Veit; Quintana, Francisco J
Highlights: Environmental factors influence the development and course of multiple sclerosis. Infections, pollutants and low sun exposure are independent risk factors for MS. The interaction of the diet and gut microbiota shapes peripheral immune responses. AHR agonists generated by bacterial and host metabolism reach the CNS. These AHR agonists dampen autoimmune inflammation in the CNS via AHR in astrocytes. Abstract : Multiple sclerosis (MS) is a chronic autoimmune inflammatory demyelinating disorder of the central nervous system (CNS), which causes severe disability and requires extensive medical attention and treatment. While the infiltration of pathogenic immune cells into the CNS leads to the formation of inflammatory lesions in its initial relapsing-remitting stage, late stages of MS are characterized by progressive neuronal loss and demyelination even without continued interaction with the peripheral immune compartment. Several genetic and environmental factors modulate and influence these processes on multiple levels. Genetic variants confer a predisposition for the development of MS, but are not accessible to therapeutic intervention as of today. However, migration studies suggest that environmental factors influence disease development, activity and progression. This article reviews mechanisms of disease pathogenesis in MS and their modulation by environmental factors such as geographical localization, the gut microbiome and the diet.